Unlocking the Power of Virtual Classrooms: Exploring the Impact of Cooperative Learning, Student Engagement, and Online Learning Constraints on Learning Outcomes - Erwin, Erwin; Ariani, Farida (Jurnal Komunikasi Pendidikan, 2023)
The impact of online learning during the COVID-19 pandemic has significantly affected the activities, psychological conditions, and behavioral changes in adult learners, with technology-based learning becoming increasingly widespread in higher education institutions. Both professors and students have adapted to engage in distance learning interactions, including those at the Faculty of Tarbiyah, Islamic Institute of West Sumatra, who have become familiar with utilizing virtual classes through collaborative learning methods. This research aims to analyze the influence of implementing virtual classes with collaborative learning methods, student engagement, and the challenges faced by students in online learning on learning outcomes. The research method employed is a mixed-method convergent parallel design, involving the collection of both qualitative and quantitative data. Qualitative data analysis uses descriptive analysis, while quantitative data is analyzed using a cross-sectional study design. The research findings indicate that student learning through virtual classes at the Faculty of Tarbiyah, supported by platforms like Google Classroom, WhatsApp, and Zoom Meetings, has been effective and has positively impacted students' learning achievements. The challenges encountered by students and professors during online learning include technology mastery, cost, smooth communication, interactive success, internet signal, and time management. For the faculty members of Tarbiyah, it is recommended to conduct online learning based on virtual classes, involving various integrated platforms such as Google Classroom, WhatsApp, and Zoom Meetings. Additionally, preparing a comprehensive online learning guide with solutions to handle technical issues would be beneficial. This research contributes to the education field by providing insights into effective online learning practices and highlighting the challenges that need to be addressed to improve the overall learning experience.